About flight safety management during operation of unmanned aircraft systems - V. D. Sharov; B. P. Eliseev; P. M. Polyakov (Научный вестник МГТУ ГА)
The development of the unmanned aircraft market is hindered by the regulatory deficiencies of this aviation segment. This fully applies to the most important aspect of the activity – flight safety management. In accordance with the Standards and Recommended Practices (SARPs) ICAO and the Air Legislation of the Russian Federation, the availability of flight safety management systems (SMS) is mandatory for operators, developers and aircraft manufacturers, as well as for aircraft engines and propellers. However, this requirement does not fully apply to organizations involved in design, manufacture and operation of unmanned aircraft systems (UAS). At the same time, UAS use in various spheres of economic activities is associated with significant and diverse risks for manned aircraft, as well as vehicles, people and important infrastructure facilities on the ground. The article analyzes the current situation with the regulatory framework with relation to SMS development and implementation in the unmanned aviation segment at the international and state level and the prospects of its improvement. Based on experience, the most major methodological issues while SMS developing and implementing in various entities-aviation services providers are related to the selection, implementation and application of methods for safety risk management techniques, which have significant features for UAS operation. Considering anticipated adoption of SMS requirements in the near future, some innovative practices in this area of activity about aviation safety risk management for such entities have been reviewed.